Wide bandwidth focal plane array receiver for radio astronomy - Bukilic, Nino (Curtin University, 2010)
Reflective antennas equipped with phase array feeds (PAFs) have been proposed as part of the Square Kilometre Array reference design, since they offer a wide Field of View (FoV) and large collecting area. To achieve a contiguous FoV, and to cancel spill-over radiation, the Focal Plane Array (FPA) must sample the focal field of the reflector at least every half-wavelength at the upper operating frequency. Low-noise operation over a wide bandwidth requires appropriate impedance matching to the low-noise amplifiers, and this is a challenging research problem since the input impedance of the FPA elements can vary strongly with frequency.Advanced broadband design techniques for antenna arrays have resulted in antenna shapes getting more complex. Modelling of these antennas can only be carried out using numerical computational electromagnetic methods (CEM), and accurate modelling of complex antennas demand the full-wave analysis with fields and currents that vary in three dimensional space. The Frequency Domain Integral Equation model is adopted in this study and used via the Method of Moments (MoM) technique for simulation and modelling of the FPA. The "MoM Antenna Development Toolbox" (MoMADT), 64 bit version of the modelling software, is specifically developed in this study for designing, building and modelling of complex antenna and electromagnetic structures. MoMADT utilizes surface and volume integral equations and provides functions for generating precise meshes and accurate method of moments solutions. MoMADT enables structures to be assembled in an array formation to consist of conductive or dielectric materials, or a combination of both.Study of the wide bandwidth FPA receiver was achieved through analysis of broadband planar antenna structures. This research investigates a unique design solution for a FPA utilizing the diamond planar strip antenna elements arranged to provide three vectors of polarization (triple-polarized FPA). The most promising FPA identified is the 77 Hexagonal Diamond Tripole (HDT) array. This array yields an operating frequency range of 550 to 2100 MHz, providing bandwidth ratio of 3.8:1. It is shown that adequate impedance match can be achieved across the indicated frequency range with desired directivity and gain. In addition, the 77 HDT array offers optimized efficiency and allows the polarization to be distinguished at any angle about the axis normal to the antenna plane to within a theoretical uncertainty of ± 2.2°. This is also true for any function of the FoV allowed by the surface area of the FPA.